A selective NO sensor based on the semiconducting BC2N nanotubes: a computational study. (16th December 2020) - Liu, Yongqiu; Liu, Chao; Kumar, Ajit
Abstract : We simulated the interaction of CO and NO gases with a semiconducting BC2 N nanotube (BC2 NN) to investigate its potential application as a sensor, using DFT calculations. The CO or NO molecule adsorbed on a BC2 NN boron atom with interaction energy of −0.27 or −0.21 eV. The adsorption of CO gas cannot change the electrical conductivity, Fermi level, and work function of BC2 NN sensibly. But the adsorption of NO gas produced an electronic signal by increasing the electrical conductivity of the BC2 NN. This signal increased by rising the NO concentration. Thus, the BC2 NN might be an electronic NO gas sensor in the presence of CO molecules. The predicted recovery time for NO desorption is 0.6  ns at room temperature. Furthermore, we showed that the BC2 NN is insensitive to O2, H2 O, NH3, CO2, and N2 gases. GRAPHICAL ABSTRACT: